The Relationship between Marketing Mix Strategies and Customer Loyalty: A Study in Food and Beverage Sector - Muhammad Hafiz, Azizan (2010)
This study is carried out to investigate the relationship between marketing mix strategies and customer loyalty. The study is focusing on food and beverages products. The outcomes of this research are essential to readers in order to understand the dimension that influences customer to buy the products. Furthermore, the dimension is important to recognize the relationship of the marketing mix strategy which consists of 4p's such as products, pricing, promotion and distribution towards customer loyalty. Quantitative method is used in this study. The respondents come from 170 students at Kolej Universiti Insaniah (KUIN), Alor Setar. The result shows there are significant relationship between product, pricing, promotion and distribution towards customer loyalty. Future research reveals there is significant relationship between marketing mix strategy and customer loyalty. Marketing mix strategies represent certain variance of customer loyalty. The loyalty influenced by dimension of products, price, promotion and distribution.